Pengaruh Latihan Sepak Bola Menggunakan Punggung Kaki Bagian Dalam Terhadap Ketepatan Shooting Ke Gawang - Ayello, Onesimus; Anwar, Saiful (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study aims to determine the effect of soccer training using the inside of the instep on shooting accuracy at goal in PS Unimuda Sorong players. The research method used was a quasi-experiment with a pre-test and post-test design in two experimental groups. The research sample consisted of 23 players selected using total sampling technique. The results of data analysis showed that there was a significant increase in shooting accuracy after being treated with variations of training using the inside of the instep for 16 sessions. The average value of shooting accuracy increased from 28.0 in the pre-test to 39.0 in the post-test, with an increase of 39.29%. Based on the research results, it was concluded that training using the inside of the instep was effective in increasing shooting accuracy.